Corifollitropin- α compared to daily r-FSH in for patients undergoing intracytoplasmic sperm injection: Clinical trial study - Ziba Zahiri Sorouri; Davoud Pourmarzi; Niloufar Safar Khah (Shahid Sadoughi University of Medical Sciences, 2019)
Background The current treatment regimen for ovarian stimulation in Intracytoplasmic sperm injection (ICSI) patients is daily injections of Gonadotropins. Recombinant DNA technologies have produced a new recombinant molecule that is a long-acting Follicle Stimulating Hormone (FSH), named corifollitropin alfa. A single injection of long-acting FSH can replace seven daily FSH injections during the first week of controlled ovarian stimulation (COS) and can make assisted reproduction more patients-friendly. There is limited data with different results in this area. Objective To compare the effectiveness of long-acting FSH vs. daily r-FSH in terms of pregnancy and safety outcomes in women undergoing ICSI cycles. Materials and Methods In this clinical trial study, 109 women who were the candidates for ICSI at azzahra hospital were divided in two groups. The first group received 150 units of daily Gonal-f from second or third day of menstruation. The second group received a 150IU corifollitropin alfa on the second or third day of mensuration, and the treatment continued from day eighth of stimulation with Gonal-f based on the ultrasound finding. Both the groups received GnRH antagonist from fifth day of stimulation. Two groups were compared in terms of number of dominant follicles, number of oocytes, stimulation duration, total number of embryos, number of transferred embryos, and success rate of pregnancy. Results No significant difference was found between the two groups in terms of stimulation duration, number of follicles, number of oocytes, total number of embryos, and number of transferred embryos. Moreover, pregnancy outcomes including chemical pregnancy rate (positive pregnancy test), clinical pregnancy rate (detection of fetal heart), the rate of ovarian hyper-stimulation syndrome, multiple-pregnancy, ectopic pregnancy, and miscarriage didn't have a significant difference between the two groups. Conclusion As corifollitropin alfa was as effective as r-FSH, it could be used as an alternative to ovulation stimulation method in patients undergoing ICSI.